The Challenges of Implementing the Independent Curriculum in Indonesian Language Learning in Elementary School High Classes - Setiawan Edi Wibowo; Bambang Saptono; Agung Hastomo; Herwin; Amalia Rizki Ardiansyah (Jurnal Ilmiah Sekolah Dasar, 2023)
The confusion in the independent curriculum started from the teachers' need to understand the learning outcomes set by the government. It also impacts their multiple interpretations of the preparation of learning tools and their embodiment in their respective classes. Therefore, this study aims to analyze the application of the independent curriculum in higher grades, especially in implementing the project-based learning model in Indonesian subjects. This research is a phenomenological qualitative research. The research subjects were selected based on purposive considerations. The selection of informants used knowledge and competency criteria related to the application of project-based learning to the prototype curriculum in driving schools in Yogyakarta. Data collection techniques used are observation and documentation. At the same time, the data analysis technique uses qualitative-interactive analysis techniques. The results of this study indicate that the problem of implementing the independent curriculum in the upper grades of elementary schools is the problem of the flow of learning objectives that occurs in the adaptation of teachers from implementing the 2013 curriculum to an independent curriculum. Several problems in implementing the independent curriculum in Indonesian language learning in elementary school high grades, namely problems in aspects of the flow of learning objectives, problems in learning scenarios, and problems in student worksheets.